The effects of AST-120 on chronic kidney disease progression in the United States of America: a post hoc subgroup analysis of randomized controlled trials - Schulman, Gerald; Berl, Tomas; Beck, Gerald J.; Remuzzi, Giuseppe; Ritz, Eberhard; Shimizu, Miho; Shobu, Yuko; Kikuchi, Mami (BMC nephrology, 2016)
The orally administered spherical carbon adsorbent AST-120 is used on-label in Asian countries to slow renal disease progression in patients with progressive chronic kidney disease (CKD). Recently, two multinational, randomized, double-blind, placebo-controlled, phase 3 trials (Evaluating Prevention of Progression in Chronic Kidney Disease [EPPIC] trials) examined AST-120’s efficacy in slowing CKD progression. This study assessed the efficacy of AST-120 in the subgroup of patients from the United States of America (USA) in the EPPIC trials.